Consumo de alimentos e bebidas selecionadas e níveis séricos de ácido úrico em adultos - ELSA- BRASIL (2008-2010) - Michelle Timóteo da Silva (2018)
INTRODUCTION: Higher serum levels of uric acid (UA) are associated with dysfunctions such as gout, metabolic syndrome, and others. Evidence suggests that some foods and beverages may influence serum levels of UA, but results are inconsistent. OBJECTS: To investigate the association between daily consumption of selected food groups and beverages and the serum level of UA. METHODS: Cross-sectional study with baseline data from the Longitudinal Study of Adult Health (ELSA-Brazil), a multicentre cohort of 15,105 servants aged between 35 and 74 years. Participants in the use of Allopurinol and Benzbromarone, who underwent bariatric surgery and who presented extreme caloric consumption, totaling 14,381 participants were excluded. Food consumption was evaluated through a food frequency questionnaire containing 114 items. The association between consumption of each of the food groups (servings / day) and serum AU (mg / dL) and hyperuricemia (AU≥6.8 mg / dL) was investigated by means of multiple linear and logistic regression, respectively . RESULTS: There was an inverse association between the consumption of dairy products and the serum level of UA, with a clear dose-response gradient after adjustments. The high meat intake was associated with the high serum level of UA in women and the high consumption of viscera in men. The consumption of fish and fruits, vegetables and vegetables was not associated to UA. In men, moderate and high consumption of beer and distillates, but not wine, was associated with a high serum level of UA. In women, only beer consumption was associated with increased serum levels of UA. CONCLUSION: Healthy behaviors as higher consumption of dairy products were associated with lower serum levels of UA suggesting potential benefits. Risk behaviors such as high alcohol consumption of different types were associated with higher levels of UA.